THE SIGN READING OF THE STRUCTRE OF UNIFICATION IN THE CIVILIZATION OF MESOPOTAMIA: جهينة حامد حساني (Al-Academy, 2015)
The Mesopotamian artist conversed the functions of idols with multi-formation, varied pictured and structural significances sign momentum. Each phenomenon had an idol and each event had an idol. So multiplicity contributes in the enrichment of the Mesopotamian thought by the full and comprehensive familiarity of the characterization of the religious space which reached up to realize the start point of creation and formation and specify the concept of unification in such a way that considered as pagan multiplicity and Atheism according to what brought by most of the previous studies.Such a research as ( The Sign Reading of the Structure of Unification in the Civilization of Mesopotamia) aims to clarify this confusion through decoding the pluralism code under a supposed frame of one perspective which the artist tried to converse and address in pictures of different characterization. So we aim at narrowing the presentation into two axis:The First Axis: A research in the Structure of Unification.The Second Axis : A research in the Sign Reading.So one of the results of this study is to proof the truth of our hypothesis that the Mesopotamian civilization searched in unification since the first formations and the pluralism was for knowledge aim of the ability of Almighty Allah. So it is possible to treat these sign structures as induction functions, no more no less, Almighty Allah says in his scripture